Prose reading in neglect. - Beschin, Nicoletta; Cisari, Carlo; Cubelli, Roberto; Della Sala, Sergio (Brain & Cognition, 2014)
Prose reading has been shown to be a very sensitive measure of Unilateral Spatial Neglect. However, little is known about the relationship between prose reading and other measures of neglect and its severity, or between prose reading and single word reading. Thirty participants with a first stroke in the right hemisphere and clear symptoms of spatial neglect in everyday life were assessed with tests of prose reading (text in one column book-like, and in two columns magazine-like), single words reading, and a battery of 13 tests investigating neglect. Seventy percent of these participants omitted words at the beginning of the text (left end), showing Prose Reading Neglect (PRN). The participants showing PRN differed from those not showing PRN only for the overall severity of neglect, and had a lesion centred on the insula, putamen and superior temporal gyrus. Double dissociations emerged between PRN and single word reading neglect, suggesting different cognitive requirements between the two tests: parallel processing in single word reading vs. serial analysis in text reading. Notably, the pattern of neglected text varied dramatically across participants presenting with PRN, including dissociations between reading performance of one and two columns text. Prose reading proved a complex and unique task which should be directly investigated to predict the effects of unilateral neglect. The outcome of this study should also inform clinical assessment and advises given to patients and care-givers.